Prediction of Concomitant Nosocomial Infection in Patients Previously Colonized Colorectally by Multidrug-Resistant Bacteria in an SDD Setting - Sergio Ruiz-Santana; José Dearriba-Reyes; Pedro Saavedra; Laura Iglesias-Llorente; Laura Alonso-Acero; Carmen-Rosa Her; Catalina Sánchez-Ramírez (MDPI AG, 2024)
Background: Antibiotic resistance is a worldwide concern. This study retrospectively analyzed patients admitted to the ICU of a tertiary hospital over a period of 7 months who were rectally colonized by multidrug-resistant microorganisms. The incidence of concomitant nosocomial infections was estimated, thus providing the risk of a colonizing microorganism producing a nosocomial infection. Methods: Infections with the same microorganism (concomitant) or different microorganisms (non-concomitant) were analyzed in order to adjust the empirical antibiotic treatment. Patients with rectal colonization by at least one multidrug-resistant bacterium (MDRB) on admission or after ICU admission were included. All patients had complete selective digestive decontamination (SDD) prophylaxis. For univariate analysis, categorical variables are expressed as frequencies and percentages and continuous variables as means and standard deviations, or as medians and interquartile ranges. For multivariate analysis, the model is summarized with p-values and hazard ratios with 95% confidence intervals. Survival analysis was conducted using the Kaplan-Meier method, which was performed to evaluate the time elapsed from colonization to infection by the same bacteria. Statistical significance was considered at p < 0.05. Results: Of the 130 patients with MDRB bacterial colonization analyzed, 98 remained free of infection, while 22 developed non-concomitant infections and 10 had infections concomitant to rectal colonizing bacteria. OXA-48-producing bacteria and MDR-Pseudomonas spp. incidences were 18.9% (95% CI: 7.96-35.2) and 44.4% (CI: 13.7-78.8), respectively. Conclusions: OXA-48-producing bacteria and MDR-Pseudomonas spp. were the only bacteria associated with the development of infections concomitant to rectal colonization in an SDD setting. The incidence of MDRB infections was low.